HUBUNGAN PENGETAHUAN GIZI DAN SIKAP ANAK SEKOLAH DENGAN PERILAKU MEMILIH MAKANAN JAJANAN DI SEKOLAH MENENGAH PERTAMA (SMP) NEGERI 2 KOTA KUPANG - Yohakim Dawi; Picauly, Intje; Lewi Jutomo (Pergizi Pangan DPD NTT, 2013)
The research is of analytical survey of cross sectional study design. 90 people-school children in SMP Negeri 2 Kota Kupang in this respect, have been randomly sampled. They consist of 39 7th-grade schoolchildren 26 8th- grade school children, and 25 9th-grade school children. Questionnaire has been used to collect data, by all means the respondents themselves fill in questionnare. Each variable under research is tested according to chi square test. The test is used to find out relation between the knowledge of nutrition and the attiiude of school children with the habit of choosing makanan jajanan. The research shows no relations between the knowledge of nutrition and the attiiude of school children with the habit of choosing makanan jajanan; the value of p 0,930 (>0,05) is revealed in this case. Similarly, school children attitude on the habit of choosing makanan jajanan has no relation either. This can be seen in it’s value of p 0,788 (>0,05). It can be conculded then that there is no relation between the knowledge of nutrition and the attitude of school children with the habit of choosing makanan jajanan.